Craft The place Rubbish from Paper Used for Increase Caring Environment Students at SDN 10 Kota Barat - Annisa Fitriyani Olii; Amanda Erika Pade; Desiyanti Hamzah; Abdul Rahmat (Periodica Journal, 2022)
In implementation activity study teach customized with the learning model that has been arranged by the Guardian class . However , in the continuity of the learning model compiled by the Guardian class permanent same on every meeting so that create bored atmosphere for students , interest student in study Becomes less and no exists receptacle for student in distribute potential and abilities . Meanwhile , system quality and quality education depending on the activity ongoing learning with challenging and interesting for student . In face Thing this is needed a management strategy various classis with apply the PAKEM model. PAKEM is abbreviation from Learner Active , Creative , Effective and Fun . Type study this is study field , that is research conducted with plunge direct to field for researching influence use PAKEM method against motivation study student . Method used in study this is method experiment . Research results show that there is enhancement motivation study after using it PAKEM method in implementation study student class 4 SD N 10 Kota Barat.
Keywords: effective; fun; active; motivation